COLLECTIVE INSIGHTS ON THE POLYMORPHS, BIOAVAILABILITY, AND BINDING PROPERTIES OF ATOVAQUONE (ANTIMALARIAL DRUG): AN OVERVIEW - Saralaya, Sanjay Sukumar; Kanakamajalu , Shridhara (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
This review initiative had interrelated key aspects like crystal structure, bioavailability, and stereospecific binding capabilities of Atovaquone. Surprisingly, very little literature was available regarding the exploration of different polymorphs of Atovaquone. Interestingly, extensive literature was found towards the bioavailability features and factors specifically related with Atovaquone. Several researchers had attempted to correlate crystal morphology and orientation with the binding properties of Atovaquone and its structurally related compounds. The polymorphic stability of the molecule will play a crucial role in drug formulation and contributes towards the bioavailability of the drug through variations in solubility. Hence for Atovaquone, two factors must be considered: its polymorphic nature and the presence of stereospecific isomers to explain its bioavailability and binding properties. The trans-isomer of Atovaquone, having a specific polymorphic form had provided higher bioavailability, more efficient binding, and an expectedly higher inhibitory activity.